Prosedur Pengelolaan Produk Deposito pada PT. BPRS Amanah Bangsa - Calen Calen; Christopher Agustian; Asmawati Halilah Damanik; Arwin Tannuary (Owner : Riset dan Jurnal Akuntansi, 2019)
The Amanah Bangsa Islamic Bank Financing Bank exists and grows as a bank that is able to provide banking services based on sharia principles. As a community facility, BPRS Amanah Bangsa offers a time deposit product or often referred to as Time Deposit. Deposits at BPRS Amanah Bangsa are savings using a mudharabah contract, where the customer is called sahibul maal while the bank is the mudharib. Funds in deposits are guaranteed by the government through the Deposit Insurance Corporation (LPS) with certain conditions. Usually Deposit products have a storage period of 1, 3, 6, or 12 months according to the wishes of the customer. Deposits can also be renewed automatically when they are due until the owner withdraws the deposit. The mudharabah contract application in time deposits products at BPRS Amanah Bangsa is a contract whose management meets the mudharib (bank) responsibilities and the customer is obliged to follow the provisions given by the bank.